2017
DOI: 10.5210/fm.v22i9.8042
|View full text |Cite
|
Sign up to set email alerts
|

‘Stop Fake Hate Profiles on Facebook’: Challenges for crowdsourced activism on social media

Abstract: This research examines how activists mobilise against fake hate profiles on Facebook. Based on six months of participant observation, this paper demonstrates how Danish Facebook users organised to combat fictitious Muslim profiles that spurred hatred against ethnic minorities. Crowdsourced action by Facebook users is insufficient as a form of sustainable resistance against fake hate profiles. A viable solution would require social media companies, such as Facebook, to take responsibility in the struggle agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Collectively these studies have revealed how social media platforms create, to varying extent, enclaves within which overt or covert far-right discourses and the sorts of hate-speech underlying them can intensify, while simultaneously providing entry points to broader digitally networked audiences that allow the greater acceptance and normalisation of those same discourses (Farkas and Neumayer, 2017;Merrill and Åkerlund, 2018;Chaudhry and Gruzd, 2020). Social media platforms are thus not just neutral platforms on which racism is expressed, covertly or otherwise.…”
Section: Mediatised Nostalgia Digitised Far-right Discourse and Memementioning
confidence: 99%
“…Collectively these studies have revealed how social media platforms create, to varying extent, enclaves within which overt or covert far-right discourses and the sorts of hate-speech underlying them can intensify, while simultaneously providing entry points to broader digitally networked audiences that allow the greater acceptance and normalisation of those same discourses (Farkas and Neumayer, 2017;Merrill and Åkerlund, 2018;Chaudhry and Gruzd, 2020). Social media platforms are thus not just neutral platforms on which racism is expressed, covertly or otherwise.…”
Section: Mediatised Nostalgia Digitised Far-right Discourse and Memementioning
confidence: 99%
“…For scholars and journalists, such propaganda poses considerable challenges due to the difficulty of establishing authorship. Social media companies have so far been hesitant to provide support for such investigations, while offering extensive anonymity for content producers and handling abusive content by simply removing it [10]. This has led to a scenario in which little research has been carried out on the topic.…”
Section: State Propaganda In Digital Mediamentioning
confidence: 99%
“…Disguised human-driven accounts can neither easily be found nor traced back to an original source or controller. Furthermore, potential identification of accounts require collaboration with social media companies, which are reluctant to provide such support [10]. Within the scope of this study, Twitter has released a list of 2752 deleted accounts identified as operated by the IRA.…”
Section: State Propaganda In Digital Mediamentioning
confidence: 99%
See 2 more Smart Citations